Prevalence of GATA-3 in invasive breast cancer and its significance in predicting response to neoadjuvant chemotherapy: a tertiary center experience - Singh, Anjali; Karnik, Amit; Anand, Akshay (International Surgery Journal, 2021)
Background: GATA-3 expression was shown to be an independent predictor of overall and disease-free survival in some studies, whereas others showed no difference. We prospectively studied GATA-3 expression in index breast cancer patients and co-related with other immunohistochemical (IHC) markers along with response evaluation in IIIB onwards receiving neoadjuvant chemotherapy. Objective was to determine the expression of GATA-3 in Indian breast cancer tissue specimens and correlating GATA-3 expression with existing clinicopathological, radiological and immunohistochemical markers of breast cancer as well as with clinical response in breast cancer patients receiving neoadjuvant chemotherapy. Methods: It was a prospective study that was conducted from November 2016 to October 2017. GATA-3 expression in carci-noma breast tissue obtained by tru-cut biopsy was studied by IHC. Results: The distribution of GATA-3 receptor positivity with age showed higher positivity (p=0.79) with the older age group. The distribution of biological receptors in breast cancer patients had shown the highest presence of GATA-3 (87.5%) followed by HER2/neu (62.5%), ER (60%) and PR (50%). GATA-3 receptor positivity showed maximum positivity with luminal A subtype (50 and 9.11=59.1%) followed by HER2/neu enriched subtype (48.9%). Triple-negative breast cancer patients showed 48% positivity for the GATA-3 receptor. GATA-3 receptor expression was more in the locally advanced stage of breast cancer as compared to the early stage (p=0.02). GATA-3 positive patients showed partial response to chemotherapy (75.8%). Conclusions: There is a raised possibility that GATA-3 or its downstream genes could be used in the management of luminal breast cancer.